UJI IN VITRO AKTIVITAS ANTIBAKTERI EKSTRAK CANGKANG BIJI KARET DAN BIJI KARET TERHADAP Aeromonas hydrophila - Hilma Putri Fidyandini; Lisa Silviana (Jurusan Akuakultur, Universitas Bangka Belitung, 2021)
Catfish is one of leading fishery commodity in Indonesia that nowadays is using intensive technology. One of the problems in cultivating catfish is the invasion of bacteria Aeromonas hyprophila which can cause Motile Aetomonas Septicemia disease. Information regarding the antibacterial activity of shell and rubber seed extract on Aeromonas hydrophila is not yet known. Therefore it is necessary to do a research about the antibacterial activities of the shell and rubber seed extract against the pathogenic bacteria, Aeromonas hydrophila. This research method was sample preparation, extraction, phytochemical test, preparation of bacterial suspension, antibacterial test with agar diffusion method, minimum inhibitory concentration test. The result shows that the rubber seed shell extract contains antibacterial compounds such as saponin, terpenoids and flavonoids. While the rubber seed extract contains terpenoid and flavonoid compounds. The shell and rubber seed extract at a concentration of 0.5-4 mg/mL showed very weak inhibition.